Tethered-variable C(L) bispecific IgG: an antibody platform for rapid bispecific antibody screening - Kim, Hok Seon (Protein Eng Des Sel, 2017)
Bispecific antibodies offer a clinically validated platform for drug discovery. In generating functionally active bispecific antibodies, it is necessary to identify a unique parental antibody pair to merge into a single molecule. However, technologies that allow high-throughput production of bispecific immunoglobulin Gs (BsIgGs) for screening purposes are limited. Here, we describe a novel bispecific antibody format termed tethered-variable C(L)BsIgG (tcBsIgG) that allows robust production of intact BsIgG in a single cell line, concurrently ensuring cognate light chain pairing and preserving key antibody structural and functional properties. This technology is broadly applicable in the generation of BsIgG from a variety of antibody isotypes, including human BsIgG1, BsIgG2 and BsIgG4. The practicality of the tcBsIgG platform is demonstrated by screening BsIgGs generated from FGF21-mimetic anti-Klotho-β agonistic antibodies in a combinatorial manner. This screen identified multiple biepitopic combinations with enhanced agonistic activity relative to the parental monoclonal antibodies, thereby demonstrating that biepitopic antibodies can acquire enhanced functionality compared to monospecific parental antibodies. By design, the tcBsIgG format is amenable to high-throughput production of large panels of bispecific antibodies and thus can facilitate the identification of rare BsIgG combinations to enable the discovery of molecules with improved biological function.